Britain's Hoverflies : A Field Guide - Revised and Updated Second Edition - Ball, S. G.; Morris, R. K. A. (Roger K. A.) (WildGuides., 2015)
Britain's Hoverflies is a beautifully illustrated photographic field guide to the hoverflies of Britain, focusing on the species that can be most readily identified. It is the perfect companion for wildlife enthusiasts, professional ecologists and anyone else with an interest in this fascinating group of insects, and is designed to appeal to beginners and experts alike. Accessible, authoritative and easy to use, this book contains hundreds of remarkable photographs of the various life stages of those species that can be identified by eye or with a magnifying glass, with coverage of at least one representative from each of the British genera. It also features an essential guide to the hoverfly tribes. Detailed species accounts summarize the species' status, highlight the key identification features, provide notes on behaviour and habitat requirements and include flight-period charts and up-to-date distribution maps. Sections on hoverfly biology, where and when to look for hoverflies, legislation and conservation, photographing hoverflies, recording hoverflies and gardening for hoverflies are also included.